2021
DOI: 10.1098/rstb.2020.0396
|View full text |Cite
|
Sign up to set email alerts
|

Even violins can cry: specifically vocal emotional behaviours also drive the perception of emotions in non-vocal music

Abstract: A wealth of theoretical and empirical arguments have suggested that music triggers emotional responses by resembling the inflections of expressive vocalizations, but have done so using low-level acoustic parameters (pitch, loudness, speed) that, in fact, may not be processed by the listener in reference to human voice. Here, we take the opportunity of the recent availability of computational models that allow the simulation of three specifically vocal emotional behaviours: smiling, vocal tremor and vocal rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 57 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…( At present, in the vocal music teaching of normal colleges in our country, most of the students only stay on the evaluation of vocal music training and singing, and most of the students stay on the evaluation of skills, resulting in a single and narrow knowledge structure in the field of vocal music [18,19]. Now with a final exam to determine the score, it will let teachers and students lose a lot of opportunities to expand teaching content and improve learning in the teaching process, but also sacrificed a lot of poor basic conditions of the general students of vocal music learning interest, making the realization of teaching goals became an empty talk.…”
Section: Related Workmentioning
confidence: 99%
“…( At present, in the vocal music teaching of normal colleges in our country, most of the students only stay on the evaluation of vocal music training and singing, and most of the students stay on the evaluation of skills, resulting in a single and narrow knowledge structure in the field of vocal music [18,19]. Now with a final exam to determine the score, it will let teachers and students lose a lot of opportunities to expand teaching content and improve learning in the teaching process, but also sacrificed a lot of poor basic conditions of the general students of vocal music learning interest, making the realization of teaching goals became an empty talk.…”
Section: Related Workmentioning
confidence: 99%
“…If this model accurately portrays the evolution of musicality and its role in complex human vocal communication, musicality could be partially a fossil of our musical brain, whose original communicative purpose was bonding and communication between parents and infants, primarily through expressive pitch contours, and later the social communication of intentions and emotions (see [ 195 ] in part I, who shows how vocal cues of expressivity also drive the perception of emotion in music) to promote social bonding and coordination (music-like protolanguage) through an increased importance and precision of rhythm. It is important to emphasize the word partially , because the original purpose of aiding communication and bonding between parents and infants is still biologically relevant today in IDS and lullabies, as well as its power to promote group cohesion and social identity, evident today in ritual music, for example.…”
Section: Towards a Model For The Evolution Of Musicalitymentioning
confidence: 99%
“…Notably, by focusing on musicality, the proposed model allows for the possibility that musicality may predate music. Moreover, alongside evidence that vocal cues of expressivity also drive the perception of emotion in music [5] and that pitch modulation plays a role in human mating [1], the model illustrates that musicality is important beyond the realm of music, playing a role in domains like infant-directed speech [6,13], courtship and other language abilities.…”
Section: (B) Partmentioning
confidence: 89%
“…From the perceiver's side, past studies have shown that changes in pitch, loudness and speed are linked to perceptions of emotion in vocal signals, but interestingly, also in instrumental music. Bedoya et al [5] (critical topics (i) and (v)) take this one step further to show that voice-specific markers of emotion, such as vocal tremor, roughness and the sound of smiling, can be applied to musical stimuli to evoke analogous affective judgements. For example, musical sounds manipulated to feature the acoustic signature of a smiling voice are perceived as more positive, while musical sounds perceived to include more roughness, like the sounds of harsh screams, are perceived as relatively more negative.…”
Section: Topics and Articlesmentioning
confidence: 99%
See 1 more Smart Citation